2020
DOI: 10.21203/rs.2.17797/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of the regulatory networks and hub genes controlling alfalfa floral pigmentation variation using RNA-sequencing analysis

Abstract: Background: To understand the gene expression networks controlling flower color formation in alfalfa, flowers anthocyanins were identified using two materials with contrasting flower colors, namely Defu and Zhongtian No. 3, and transcriptome analyses of PacBio full-length sequencing combined with RNA sequencing were performed, across four flower developmental stages.Results: Malvidin and petunidin glycoside derivatives were the major anthocyanins in the flowers of Defu, which were lacking in the flowers of Zho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Quintana et al [30] suggested that there is a mutation in the early stage of the anthocyanin pathway, leading to no anthocyanidins in white flowers of Anagallis monellin. Duan et al [11] reported that malvidin and petunidin were detected in purple alfalfa flowers, whereas no color anthocyanidins occurred in cream alfalfa flowers. In this study, we found that 6 types of common anthocyanin pigments were present simultaneously in white flowers of S. miltiorrhiza.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quintana et al [30] suggested that there is a mutation in the early stage of the anthocyanin pathway, leading to no anthocyanidins in white flowers of Anagallis monellin. Duan et al [11] reported that malvidin and petunidin were detected in purple alfalfa flowers, whereas no color anthocyanidins occurred in cream alfalfa flowers. In this study, we found that 6 types of common anthocyanin pigments were present simultaneously in white flowers of S. miltiorrhiza.…”
Section: Discussionmentioning
confidence: 99%
“…The biosynthesis of anthocyanin is catalyzed by a series of enzymes in the phenylpropanoid and flavonoid biosynthetic pathways [7,8]. The genes involved in the biosynthesis of anthocyanin have been reported in many plant species such as Arabidopsis [9], spinach [10], and alfalfa [11]. Studies have found that color mutations are often found in fruits, flowers, and leaves.…”
Section: Introductionmentioning
confidence: 99%